Nrf2 regulates the expression of the peptide transporter PEPT1 in the human colon carcinoma cell line Caco-2 - Geillinger, Kerstin E.; Kipp, Anna P.; Schink, Kristin; Röder, Pia V.; Spanier, Britta; Daniel, Hannelore (Biochimica et biophysica acta, 2014)
PEPT1 is a rheogenic transport protein in the apical membrane of intestinal epithelial cells capable of transporting essentially all possible di- and tripeptides that are generated from the luminal protein breakdown. In addition, several anticancer, antimicrobial and antiviral drugs are taken up from the intestinal lumen via PEPT1 and therefore PEPT1 is a target for efficient drug delivery via prodrug approaches. Thus, understanding PEPT1 gene regulation is not only of importance for dietary adaptation but also for drug treatment. In silico analysis of the Pept1 promoter was performed using MatInspector. Pept1 promoter constructs were generated and cotransfected with an Nrf2 expression plasmid. Caco-2 cells were stimulated with Nrf2 inducers followed by electrophoretic mobility shift assay (EMSA) and chromatin immunoprecipitation (ChIP). Biological relevance was investigated using western blot analysis and transport activity assays. Reporter gene assays showed transcriptional activation of the Pept1 promoter in response to Nrf2 overexpression. EMSA as well as ChIP analysis validated Nrf2 binding to the ARE located closest to the start codon (Pept1-ARE1). Induction of the Nrf2 pathway resulted in increased endogenous PEPT1 protein abundance as well as transport activity. Moreover, we demonstrate that also the induction of autophagy by MG132 resulted in elevated Nrf2 binding to Pept1-ARE1 and increased PEPT1 protein expression. In summary, we identified a biologically active Nrf2 binding site within the Pept1 promoter which links Pept1 to the cellular defense program activated by Nrf2. This study identifies Pept1 as an inducible target gene of the Nrf2 pathway.